2008 Eighth International Conference on Peer-to-Peer Computing 2008
DOI: 10.1109/p2p.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-Peer Traffic in Operator Networks

Abstract: This paper examines the issues encountered by network operators when content providers utilize peer-to-peer (P2P) technologies to distribute media. After outlining the various causes of the conflict a set of potential solutions are presented. BackgroundP2P technologies are increasingly being used for legal distribution of media content. The generated traffic consists of bandwidth intensive file downloads as well as video streams, examples include Joost [2] and BBC's iPlayer [1]. For fixed broadband network ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It can be seen from Figure 6(a) that the link mn has a very high utilization of up to 99% for TC-0 (note that node N hosts a P-GW). It is observed that this high utilization is caused by the tromboning effect [6], which is prevalent in centralized mobile network architectures. The utilization of this link drops dramatically to around 18% in TC-1 due to the loadaware optimized placement of softEPC functions in the GPNs.…”
Section: Access Nodesmentioning
confidence: 99%
“…It can be seen from Figure 6(a) that the link mn has a very high utilization of up to 99% for TC-0 (note that node N hosts a P-GW). It is observed that this high utilization is caused by the tromboning effect [6], which is prevalent in centralized mobile network architectures. The utilization of this link drops dramatically to around 18% in TC-1 due to the loadaware optimized placement of softEPC functions in the GPNs.…”
Section: Access Nodesmentioning
confidence: 99%
“…Two groups of solutions can be found here, that is locality awareness and network caching [2]. While the latter method can be performed by an operator alone, the former is done by peers with the carrier cooperation.…”
Section: Previous Workmentioning
confidence: 99%
“…The unawareness of the underlying IP network related to P2P systems causes inoptimality of traffic flows in operators' networks [2], and is also responsible for undesirable interdomain (inter-carrier) traffic generating large costs. Additionally, random connectivity observed in those networks is suboptimal in the sense of the performance (download/completion time) that could be improved if P2P clients are connected having knowledge of their distance, network characteristics, geographical or networking localization.…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of this traffic is exchanged between different domains. It is a real problem for ISPs (Internet Service Providers) [2], because of the possibility of congestion on inter-domain links and also due to high costs of such links.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two basic groups of solutions that allow a decrease of the volume of the inter-domain traffic: locality (proximity) awareness and network caching [2]. In both cases a portion of the traffic is exchanged within ISP's domain instead of being transfered between various domains.…”
Section: Introductionmentioning
confidence: 99%